EVALUASI PENGGUNAAN SUCKER ROD PUMP PADA SUMUR X LAPANGAN KALREZ - Nur Fonisa Kabakoran; Gerry Nirmala; Noce.N. Tetelepta (Journal Mechanical Engineering, 2023)
Petroleum is a very important energy source because oil has a very significant role in meeting world energy. So, when producing petroleum, you need to pay close attention, for this reason an evaluation will be carried out so that you can find out the efficiency of the pump and the strength of the well production.  In the Kalrez Bula field there are petroleum production activities using the sucker road pump (SRP) method. Based on research conducted on the Sucker Rod Pump installed using the Inflow Performance Relationship (IPR) approach for well X, the q max price was obtained at 114.3081 bfpd. Meanwhile, the results of the previous well test were 100 bfpd at a pwf of 70,031 psi with a water cut of 80%, where from the results of the evaluation that had been carried out it was concluded that the pump used in well X with type 20-150 RWAC pump insert was still in place. under optimal circumstances.  Keywords: Artificial lift method,  Sucker Rod Pump, IP